Classifying Complications: Assessing Adult Spinal Deformity 2-Year Surgical Outcomes. Issue 7 (October 2020) - Klineberg, Eric O.; Passias, Peter G.; Poorman, Gregory W.; Jalai, Cyrus M.; Atanda, Abiola; Worley, Nancy; Horn, Samantha; Sciubba, Daniel M.; Hamilton, D. Kojo; Burton, Douglas C.; Gupta, Munish Chandra; Smith, Justin S.; et al.
Study Design: Retrospective review of prospective database. Objective: Complication rates for adult spinal deformity (ASD) surgery vary widely because there is no accepted system for categorization. Our objective was to identify the impact of complication occurrence, minor-major complication, and Clavien-Dindo complication classification (Cc) on clinical variables and patient-reported outcomes. Methods: Complications in surgical ASD patients with complete baseline and 2-year data were considered intraoperatively, perioperatively (<6 weeks), and postoperatively (>6 weeks). Primary outcome measures were complication timing and severity according to 3 scales: complication presence (yes/no), minor-major, and Cc score. Secondary outcomes were surgical outcomes (estimated blood loss [EBL], length of stay [LOS], reoperation) and health-related quality of life (HRQL) scores. Univariate analyses determined complication presence, type, and Cc grade impact on operative variables and on HRQL scores. Results: Of 167 patients, 30.5% (n = 51) had intraoperative, 48.5% (n = 81) had perioperative, and 58.7% (n = 98) had postoperative complications. Major intraoperative complications were associated with increased EBL ( P < .001) and LOS ( P = .0092). Postoperative complication presence and major postoperative complication were associated with reoperation ( P < .001). At 2 years, major perioperative complications were associated with worse ODI, SF-36, and SRS activity and appearance scores ( P < .02). Increasing perioperative Cc score and postoperative complication presence were the best predictors of worse HRQL outcomes ( P < .05). Conclusion: The Cc Scale was most useful in predicting changes in patient outcomes; at 2 years, patients with raised perioperative Cc scores and postoperative complications saw reduced HRQL improvement. Intraoperative and perioperative complications were associated with worse short-term surgical and inpatient outcomes.